Factors Related To The Health Complaints Of Farmers Using Pesticides In Ajinembah Village, Kecamatan Merek, Karo District, In 2022 - Seri Asnawati Munthe Munthe; Yeyen Permata Sari; Lia Rosa Veronika Sinaga; Jasmen Manurung (TOUR HEALTH JOURNAL, 2022)
Background: Farmers have long used pesticides in an effort to control pests in vegetable and fruit crops. The use of pesticides aims to increase production in the hope that plants will avoid pests and diseases. In the highlands the use of pesticides on vegetable and fruit plants is considered too intensive, because hams and plant diseases in cool climate conditions with high rainfall and humidity are good conditions for breeding. Purpose: This study aims to determine the relationship age, spraying technique, spraying time with health complaints to farmers spraying pesticides in the community in Ajinembah Village, Brand District, Karo Regency. Method: This type of research is descriptive and quantitative in nature and uses a cross-sectional approach. The research population consisted of 67 farmers who were interviewed. Data analysis used univariate analysis and bivariate analysis with chi-square test statistics. Resutls: The results of statistical tests show that the relationship between age and health complaints in Ajinembah Village has a p-value of 0.039 where the value is <0.05 which means that there is a relationship between age and health complaints. The relationship between the time of spraying and health complaints in Ajinembah Village has a p-value of 0.013 where the value is <0.05 which means that there is a relationship between the time of spraying and health complaints. The relationship between spraying technique and health complaints has a p-value of 0.000 where the value is <0.05 which means that there is a relationship between spraying technique and health complaints. Discussion and Conclusion: It is hoped that farmers will spray according to the direction of the wind to reduce health complaints.